Pengaruh Kreatifitas Guru Pendidikan Agama Islam dan Hasil Belajar Siswa terhadap Resiliensi Siswa di SMKN 5 Jember - Habibah, Nur Faiz (Momentum : Jurnal Sosial dan Keagamaan, 2018)
Abstract: At school, the Educator figure is the key person. The teacher has the moral right to guide and direct students to become knowledgeable human beings in the future. The desired goals for the process, the results of the work of students and have different for each individual. Different positive and negative traits for the development of student learning. Problems that occur in the world of education, especially problems that occur in individual students that affect the learning process. This study aims to examine the variables in the study that have been formulated in the formulation of the problem, namely whether there is an influence of PAI Teacher Creativity (), and Student Learning Outcomes (), on Student Resilience (Y). Sampling in this study was conducted with a random sampling technique with a total of 294 students from a population of 1900 students at SMK 5 Jember. The analysis carried out using regression analysis. Hypothesis testing was carried out with the help of the Statistical Statistical Package for Science (SPSS) software version 23. The results of the analysis showed that there was a significant effect between the variables of educational teacher creativity and student learning outcomes on student resilience. Thus the creativity of Islamic religious education teachers and student learning outcomes has a considerable contribution to student resilience, so teachers are needed and the values ​​obtained are good, it will make the process of student resilience both inside and outside the school environment.